2008
DOI: 10.1152/ajpheart.00331.2008
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme-2 confers endothelial protection and attenuates atherosclerosis

Abstract: dothelium plays a central role in the maintenance of vascular homeostasis. One of the main effectors of endothelial dysfunction is ANG II, and pharmacological approaches to limit ANG II bioactivity remain the cornerstone of cardiovascular therapeutics. Angiotensin converting enzyme-2 (ACE2) has been identified as a critical negative modulator of ANG II bioactivity, counterbalancing the effects of ACE in determining net tissue ANG II levels; however, the role of ACE2 in the vasculature remains unknown. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
258
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(273 citation statements)
references
References 20 publications
9
258
0
6
Order By: Relevance
“…80,81 Corroborating these findings, Tesanovic et al 82 recently reported that long-term Ang-(1-7) treatment induces atheroprotective effects in ApoE À/À mice, the most widely used animal model for atherosclerosis. According to the authors, the improvement in endothelial function resulted from an increase in NO bioavailability, as the heptapeptide increased NOS expression and decreased À production.…”
Section: Redox-sensitive Signaling By the Ace2-ang-(1-7)-mas Axismentioning
confidence: 94%
See 1 more Smart Citation
“…80,81 Corroborating these findings, Tesanovic et al 82 recently reported that long-term Ang-(1-7) treatment induces atheroprotective effects in ApoE À/À mice, the most widely used animal model for atherosclerosis. According to the authors, the improvement in endothelial function resulted from an increase in NO bioavailability, as the heptapeptide increased NOS expression and decreased À production.…”
Section: Redox-sensitive Signaling By the Ace2-ang-(1-7)-mas Axismentioning
confidence: 94%
“…Concurrently, it was recently shown that genetic deletion of ACE2 significantly increases 83 plaque formation in atherosclerotic animals, which is decreased by targeted vascular ACE2 overexpression. 80,84 Consequently, these actions of the ACE2-Ang-(1-7)-Mas axis may be exploited in the treatment of atherosclerosis and other vascular diseases.…”
Section: Redox-sensitive Signaling By the Ace2-ang-(1-7)-mas Axismentioning
confidence: 99%
“…Oligonucleotide primers for human visfatin were designed from the GeneBank databases (NM_005746) using the ProbeFinder software (Roche Applied Science): (forward) 5Ј-AGGGCTTTGTCATTCCCAGA and (reverse) 5Ј-TGGCCACTGTGATTGGATACC. Primer sequences for eNOS and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) have been reported previously (10,13). For each PCR assay, standard curves were prepared by serial dilutions of cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with azilsartan or Ang-(1-7) attenuated neointimal area, vascular smooth muscle cell proliferation, and superoxide anion, and increased ACE2 mRNA and AT 2 receptor mRNA but not AT 1 receptor mRNA, suggesting blockade of AT 1 receptor coud enhance the activities of the ACE2/ AngⅡ/AT 2 Axis and ACE2/Ang-(1-7)/Mas Axis. The role of ACE2 in the vasculature is also reported, evaluating angiogenesis and atherosclerosis in endothelial cells of apoprotein E-knockout, ACE2-overexpressing and deficient mice [45]. ACE2-deficient mice exhibited impaired endothelium-dependent relaxation.…”
Section: Ace2/ Ang-(1-7)/ Mas Axismentioning
confidence: 99%